2017
DOI: 10.1115/1.4037158
|View full text |Cite
|
Sign up to set email alerts
|

The Estimates of the Mean First Exit Time of a Bistable System Excited by Poisson White Noise

Abstract: We propose a method to find an approximate theoretical solution to the mean first exit time (MFET) of a one-dimensional bistable kinetic system subjected to additive Poisson white noise, by extending an earlier method used to solve stationary probability density function. Based on the Dynkin formula and the properties of Markov processes, the equation of the mean first exit time is obtained. It is an infinite-order partial differential equation that is rather difficult to solve theoretically. Hence, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It has been successfully applied to analyze the stochastic behaviors of the ecosystem under stochastic continuous excitations [18,19,22,37]. In recent years, the stochastic averaging method has been generalized to investigate the nonlinear system with random jump excitations [38][39][40][41]. In the following section, we will employ the stochastic averaging method to study stochastic dynamics of the ecosystem (7).…”
Section: Stochastic Modelmentioning
confidence: 99%
“…It has been successfully applied to analyze the stochastic behaviors of the ecosystem under stochastic continuous excitations [18,19,22,37]. In recent years, the stochastic averaging method has been generalized to investigate the nonlinear system with random jump excitations [38][39][40][41]. In the following section, we will employ the stochastic averaging method to study stochastic dynamics of the ecosystem (7).…”
Section: Stochastic Modelmentioning
confidence: 99%
“…Comparing (14) and (15), such transformation function ( 1 , 2 , ) can be written by the following equation:…”
Section: Problem Formulationmentioning
confidence: 99%
“…The eigenvalue problem for a differential operator of three independent variables 1 , 2 , and will be identified from (16), in which Λ( ) is the eigenvalue and ( 1 , 2 , ) is the associated eigenfunction. Meanwhile, the eigenvalue Λ( ) is seen to be the Lyapunov exponent of the th moment of system (1) from (15). Applying the perturbation theory, both the moment Lyapunov exponent Λ( ) and the eigenfunction ( 1 , 2 , ) are expanded in power series of ; that is,…”
Section: Moment Lyapunov Exponentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the dynamic systems without time-delay, Wang et al investigated the stochastic resonance in a FitzHugh-Nagumo model with an additive Lévy noise numerically; the numerical simu-lation results show the occurrence of the stochastic resonance phenomena in the given FHN system [12]. Xu et al proposed a method to find an approximate theoretical solution to the mean first exit time of a one-dimensional bistable kinetic system subjected to additive Poisson white noise and derived the analytical solution to the mean first exit time by combining perturbation techniques with Laplace integral method [13]. Xu et al discussed the constructive role of combined harmonic and random excitation on stochastic resonance (SR) in a Brusselator model; the simulation results showed that the intensity of the Gaussian colored noise and the amplitude of the periodic force can enhance SR [14].…”
Section: Introductionmentioning
confidence: 99%